Primary and secondary prevention of cerebrovascular diseases in young people: an application for individually wearable gadgets as an element of the medical decision-making system - T. I. Dutova; I. N. Banin; N. A. Ermolenko; Yu. V. Lyutikov; V. O. Lavrenteva (Лечащий Врач)
Background. Cerebrovascular disorders are a real tragedy on a global scale. The number of cases of acute cerebral circulatory disorders of this type reaches 400-450 thousand per year. Of particular concern is the increase in the prevalence of ischemic strokes in young ablebodied people. In this regard, primary prevention, comprehensive diagnosis, timely and effective treatment of stroke is the most important medical and social problem. Gadgets like smart watch are becoming increasingly available and can record various types of medical data. This is a unique opportunity to monitor the health of out-patients for a long period of time.Objective. To test the possibility of implementing primary and secondary prevention programmes using a portable smart gadget in a cohort of patients with cryptogenic stroke and in people who have not suffered a stroke but have risk factors for cerebrovascular disorders.Results. A programme has been developed to register and store the data on the presence of risk factors for vascular catastrophes in patients and methods of individualized prevention. The key parameters are the data of patients' risk factors recorded in relation to the presence of each clinical symptom with the entry of information into the database according to 'many things to the one' principle. It can be used to accumulate and analyze the data on the presence of risk factors for cerebrovascular disorders, the choice of individualized prevention, and patients' management tactics.Conclusion. The use of new technologies can lead to the improvement of programmes for the prevention of cerebrovascular disorders. The latest portable smart gadgets are able to continuously monitor various vital parameters, which can radically transform the interaction between a doctor and a patient and contribute to the implementation of individually designed preventive programmes.